2016
DOI: 10.1016/j.archoralbio.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Evc2 in craniofacial tissues and craniofacial bone defects in Evc2 knockout mouse

Abstract: Objective Our objectives were to determine the expression of EVC2 in craniofacial tissues and investigate the effect of Evc2 deficiency on craniofacial bones using Evc2 knockout (KO) mouse model. Design Evc2 KO mice were generated by introducing a premature stop codon followed by the Internal Ribosomal Entry Site fused to β-galactosidase (LacZ). Samples from wild-type (WT), heterozygous (Het) and homozygous Evc2 KO mice were prepared. LacZ staining and immunohistochemistry (IHC) with anti-β-galactosidase, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…We specifically found decreases in growth axes of the upper face (E-Iu), viscerocranial length (E-Bu), erupted upper incisor length (Pr-Iu), erupted lower incisor length (Id-Ii), distance between the first molar and incisor in mandible (Ml-Ii), length of anterior cranial base (So-E), neurocranial length (Po-E), the distance between the first molar to the most posterior point (Po-Mu), and total skull length (Po-A), respectively (Figure 2A and Table 2 ). These phenotypic observations recapitulate many of the mid-facial defects of the Evc2 global mutants that we previously reported ( Badri et al, 2016a ). Additionally, we found a shallow mid-facial region in the Evc2 P0 mutants, as evidenced by decreased angle measures in nasal bone to cranial base (ANL/SoEL), maxilla-premaxilla to cranial base (MuBuL/SoEL), maxilla-premaxilla to cranial vault (MuBuL/PoEL), upper incisors to cranial base (BuEL/SoEL), and angle of cranial vault (ABrL/PoBrL), respectively (Figure 2B and Table 2 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We specifically found decreases in growth axes of the upper face (E-Iu), viscerocranial length (E-Bu), erupted upper incisor length (Pr-Iu), erupted lower incisor length (Id-Ii), distance between the first molar and incisor in mandible (Ml-Ii), length of anterior cranial base (So-E), neurocranial length (Po-E), the distance between the first molar to the most posterior point (Po-Mu), and total skull length (Po-A), respectively (Figure 2A and Table 2 ). These phenotypic observations recapitulate many of the mid-facial defects of the Evc2 global mutants that we previously reported ( Badri et al, 2016a ). Additionally, we found a shallow mid-facial region in the Evc2 P0 mutants, as evidenced by decreased angle measures in nasal bone to cranial base (ANL/SoEL), maxilla-premaxilla to cranial base (MuBuL/SoEL), maxilla-premaxilla to cranial vault (MuBuL/PoEL), upper incisors to cranial base (BuEL/SoEL), and angle of cranial vault (ABrL/PoBrL), respectively (Figure 2B and Table 2 ).…”
Section: Resultssupporting
confidence: 88%
“…Generating our own Evc2 mutant mice enabled us to characterize the pathological mechanisms leading to abnormal appendicular bone and hypomorphic enamel development ( Zhang et al, 2015 , 2016a , b ). Our subsequent studies further demonstrated the expression of Evc2 in the mid-facial regions ( Badri et al, 2016a ) and mid-facial defects in Evc2 global mutant mice ( Badri et al, 2016b ). We most recently employed a conditional, Cre -mediated approach toward deleting Evc2 in a neural crest-specific manner.…”
Section: Introductionmentioning
confidence: 71%
“…These observations are consistent with previous reports using different methods to study abnormal craniofacial development (Badri et al, 2016b) and abnormal tooth development (Zhang et al, 2015(Zhang et al, , 2017. Our previous studies demonstrated that Evc2 is expressed in nearly all tissues in the skull (Badri et al, 2016a). Because the nasal and frontal bones are developmentally derived from neural crest cells, the reasonable speculation is that Evc2 function in the neural crest cells leads to shortened nasal and frontal bones.…”
Section: Discussionmentioning
confidence: 99%
“…These include EVC2 on chromosome 4, CDK5RAP2 on chromosome 9, CRY2 on chromosome 11, ATXN2 on chromosome 12, and NUP62 on chromosome 19. EVC2 (EvC ciliary complex subunit 2) contributes to growth and development of bone and skeleton, and regulates Sonic Hedgehog pathway signaling, a pathway described as essential to NB progression 34 41 . Mutations in the EVC2 gene have been related to Ellis-van Creveld syndrome and Weyers acrofacial dysostosis 42 .…”
Section: Resultsmentioning
confidence: 99%